Studying Divorced Couples’ Lived Experiences of Social and Psychological Factors Influencing Divorce to Propose an Appropriate Conceptual Model - Kerdegar , Mitra; Barzegar, Majid; Baghooli , Hossein; Kouroshnia, Maryam (KMAN Counseling & Psychology Nexus, 2026)
This study aimed to explore the lived experiences of divorced couples to identify the underlying social and psychological factors influencing divorce and to propose an integrative conceptual model explaining its process and outcomes. The research adopted a qualitative design using the grounded theory approach based on Strauss and Corbin’s systematic method (2008). The statistical population comprised divorced couples residing in Shiraz, Iran. Participants were selected through purposive sampling according to specific inclusion criteria: at least two months and a maximum of five years since divorce, absence of severe physical illness as the main cause of divorce, and willingness to participate. Semi-structured interviews were conducted until theoretical saturation was achieved with ten couples. Data were analyzed using three levels of coding—open, axial, and selective—to identify causal, contextual, intervening, strategic, and consequential components of the divorce process. Lincoln and Guba’s (1985) criteria of credibility, transferability, confirmability, and dependability were applied to ensure trustworthiness. The results revealed that divorce is not an instantaneous or single-cause event but a gradual, multifactorial, and structured process shaped by the interplay of individual, relational, and sociocultural dynamics. Causal factors included dysfunctional family backgrounds, patriarchal gender beliefs, emotional immaturity, and poor communication. Contextual conditions, such as cultural taboos, social pressure for endurance, and lack of premarital education, intensified the process. Intervening variables, including personality traits, economic dependence, and presence of children, acted as catalysts or inhibitors. Strategies like silence, avoidance, and concealment deepened marital alienation. Consequences spanned psychological distress, social isolation, and in rare cases, identity reconstruction. Divorce in Iranian society represents a multidimensional psychosocial phenomenon rooted in cultural, emotional, and structural inequalities, requiring multi-level interventions that integrate individual, familial, and societal support systems.